Intellectual capital management for increasing innovative activity of enterprises - Aimukhanbetova , G. (BUKETOV BUSINESS REVIEW, 2019)
In the article the management of the intellectual capital of the enterprise in order to increase its innovative activity is discussed. The development of intellectual capital in conjunction with innovative activity is a key factor in the development of any enterprise in an innovative economy. The ability of an enterprise to create and use intellectual capital in its work largely determines its strategic position in domestic and foreign markets. The article defines that the innovative activity of an enterprise depends on internal and external factors. The author highlights the innovative and creative potential of employees as the main internal factor of innovative activity. The article shows that the implementation of intellectual potential in intellectual capital requires the presence of three resource components: personal, informational and innovative potentials. The transformation of intellectual potential into intellectual capital occurs in the process of vigorous activity on the use of corresponding resources and market opportunities, as a result of which intellectual capital is formed, consisting of innovative, human and structural capitals. The article shows that intellectual capital is increasingly concentrating on working with the consumer and is being used more and more effectively to provide the necessary intensity of organizational growth and development. The author examined in detail the modern model of business processes of companies, which is based on the concept of the capital structure of the company «inverted pyramid», the levels of which represent respectively: intellectual, circulating and physical capital.